VD_FINDINFO Décision / 2013 / 1 vom 6. September 2012 - VD Tribunal cantonal (2012)
DÉTENTION PRÉVENTIVE, ORDRE PUBLICEN GÉNÉRAL, RISQUE DE RÉCIDIVE | 221 al. 1 let. c CPP (CH), 222 CPP (CH), 229 CPP (CH), 393 al. 1 let. c CPP (CH)